PLACE OF SMALL AND MEDIUM SCALE ENTERPRISES IN THE GROWTH AND DEVELOPMENT OF THE NIGERIAN ECONOMY - NDUBA, Johnpaul Onyebuchi; AKAM, Ekene Benjamin; NGONADI, Anthony (Socialscientia: Journal of Social Sciences and Humanities, 2019)
The purpose of this paper is to ascertain the place of Small and Medium Enterprises “SME” in the growth and development of the Nigerian economy. The paper projected a detailed clarification of the concept SME and went ahead to discuss the role these SMEs has played in the economy of developed and developing states with emphasis on Nigeria. Adopting economic entrepreneurship theory as its framework of analysis, the study utilized descriptive method in analysing data sourced through the secondary method of data generation. The study found out that SMEs plays a key role in the growth and development of the Nigerian economy. Also, possible hindrances to the proper functionality of SMEs in Nigeria such as harsh economic conditions, unfavourable government policies, corruption, etc were enumerated; and the panacea such as elimination of multiple taxation, access to credit facilities, adequate capacity building briefly annotated.